Sprouted cowpea (Vigña unguiculata L.) seed as protein substitute in fish ball production. - Salcepuedes, Claudine Joy Jaculo (2017.)
Fish ball is a common street food among Filipinos. Enhancing its nutritional value by using cowpea seed sprouts was the main objective of this study. Substitution of Sprouted Cowpea Seed (SCS) as protein enhancer in fish ball production was conducted in a laboratory scale in three replications. Cowpea seed germinated after 34-36 hours was combined with flaked Dorado Fish at 4 levels such as (Flaked Dorado Fish: SCS) : F1 (90:10), F2 (85:15), F3 (80:20) and F4 (75:25). Rank Sum Test showed F4 as the most preferred formulation (MPF) and was more favored than the control. Moisture, protein and fiber content were 50.35%, 53.63% and 0.51% respectively. The descriptive analysis of the MPF based on a 15-cm line scale test showed the following sensory characteristics: no detectable SCS aroma, light brow color, moderately grainy mouthfeel, slightly pereceptible SCS taste and moderately hard texture. Consumer Testing of 70 respondents with ages ranging from 17-22 years old resulted to a ?like vey much? rating. This study showed that SCS was able to significantly increase the protein content of the fish ball from 40.12% to 53.63%. The moisture and fiber content of the most preferred fish ball formulation also increased significantly. SCS has enhanced the nutritional value of the fish ball.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Fish ball; Sprouted cowpea; Vigña unguiculata